2013
DOI: 10.4161/viru.25180
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of molecular mimicry candidates in human pathogenic bacteria

Abstract: Molecular mimicry of host proteins is a common strategy adopted by bacterial pathogens to interfere with and exploit host processes. Despite the availability of pathogen genomes, few studies have attempted to predict virulence-associated mimicry relationships directly from genomic sequences. Here, we analyzed the proteomes of 62 pathogenic and 66 non-pathogenic bacterial species, and screened for the top pathogen-specific or pathogen-enriched sequence similarities to human proteins. The screen identified appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 86 publications
2
75
0
Order By: Relevance
“…In structured domain mimicry, it is generally assumed that domains that are found in pathogen’s proteins and have high sequence similarity in a large portion of the domain, are likely to have been acquired by HGT, whereas mimics of short structural segments (such as repeats) or mimics with small sequence similarity or lack of structural similarity are likely to have arisen in a convergent manner (Doxey and McConkey, 2013; Elde and Malik, 2009) (Fig 4A). Since ELMs are short and easy to evolve, it was suggested that they belong to the latter category (Davey et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In structured domain mimicry, it is generally assumed that domains that are found in pathogen’s proteins and have high sequence similarity in a large portion of the domain, are likely to have been acquired by HGT, whereas mimics of short structural segments (such as repeats) or mimics with small sequence similarity or lack of structural similarity are likely to have arisen in a convergent manner (Doxey and McConkey, 2013; Elde and Malik, 2009) (Fig 4A). Since ELMs are short and easy to evolve, it was suggested that they belong to the latter category (Davey et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…One example application of motif predictions in function discovery is the identification of hostlike proteins in pathogenic organisms, or so-called 'mimicry' [52][53][54]. This feature of many pathogen proteins has been exploited by computational methods to predict novel virulence factors [52,55]. For example, Doxey and McConkey [52] predicted widespread mimicry of human extracellular matrix proteins across a diverse range of human pathogenic bacteria based on detected similarities between motifs in collagen and leucine-rich repeat proteins.…”
Section: Novel Motifs and Domain Architecturesmentioning
confidence: 98%
“…Because they are short and have a propensity to arise independently, they can also capture convergent evolution of function in unrelated proteins but are statistically difficult to predict without additional (e.g., structural) information. One example application of motif predictions in function discovery is the identification of hostlike proteins in pathogenic organisms, or so-called 'mimicry' [52][53][54]. This feature of many pathogen proteins has been exploited by computational methods to predict novel virulence factors [52,55].…”
Section: Novel Motifs and Domain Architecturesmentioning
confidence: 99%
See 2 more Smart Citations